Introduction of a Novel System for Quantitating Blood Loss After Vaginal Delivery: A Retrospective Interrupted Time Series Analysis With Concurrent Control Group. Issue 3 (September 2020) - Lumbreras-Marquez, M.; Reale, S.C.; Carusi, D.A.; Robinson, J.N.; Scharf, N.; Fields, K.G.; Farber, M.K.
Abstract : ( Anesth Analg . 2020;130:857–868) The most preventable cause of maternal mortality worldwide is postpartum hemorrhage (PPH). Timely detection of abnormal bleeding is critical for the treatment of PPH, and the National Partnership for Maternal Safety (NPMS) recommends quantitative measurement of cumulative blood loss, as visual estimation leads to both a 30% to 50% underestimation of blood loss and a subsequent increase in the magnitude of the hemorrhage. Gravimetry is recommended by the NPMS for measuring blood loss, but as it is a multistep process involving calculation and cumulative recording, it proves difficult to perform amidst an acute bleeding circumstance. The authors hypothesized that in vaginal deliveries (VDs), the transition from visual estimation of blood loss (vBL) to gravimetric and volumetric estimation of blood loss (tBL) would yield increased odds of immediate PPH detection. This hypothesis was based on the primary aim of finding the change in odds of immediate PPH detection in VDs before and following the implementation of the tBL device [using cesarean deliveries (CDs) as a concurrent control group]. The primary outcome of the study was detection of immediate PPH (≥500 mL vBL or tBL immediately following VD, or ≥1000 mL vBL immediately following CD). Total blood loss, blood loss ≥1000 mL, secondary uterotonic use, and a composite outcome related to PPH management (such as transfusion) before and after tBL implementation were all secondary outcomes.